An exploratory component analysis of emotion regulation strategies for improving emotion regulation and emotional eating. (1st July 2020) - Juarascio, Adrienne S.; Parker, Megan N.; Manasse, Stephanie M.; Barney, Jennifer L.; Wyckoff, Emily P.; Dochat, Cara
Abstract: Emotion-focused treatments are generally efficacious for improving emotion regulation and consequently, improving clinical symptoms across numerous disorders. However, emotion-focused treatment approaches often contain numerous treatment components, limiting our ability to identify which are most efficacious. As such, the current pilot study sought to isolate three components common across a range of emotion-focused treatments (i.e. emotional awareness, emotion down-regulation, and distress tolerance) and test the impact of each component on (1) emotion regulation and (2) emotional eating behavior. Adults ( N = 76) who reported four or more emotional eating episodes in the past month were assigned to attend a one-time, three-hour workshop focused on either awareness, down-regulation or tolerance of emotions, and were subsequently evaluated at one-week and two-weeks follow-up. All groups experienced equivalent improvements in emotional eating at two-weeks follow-up ( F [1.47, 85.38 ] = 7.60, p < .01). However, groups showed differential patterns of change across facets of emotion regulation. Improvements in access to healthy emotion regulation strategies was moderately related to improvements in emotional eating in Down-Regulation and Distress Tolerance groups ( r [18] = 0.40, r [20] = 0.63, respectively). In the Distress Tolerance group, improvements in emotional eating were moderately related to improvements in acceptance of emotions ( r [20] = 0.33) and ability to refrain from impulses ( r [20] = 0.41). In the Emotional Awareness group, improvements in emotional acceptance ( r [20] = 0.30), awareness ( r [20] = 0.38) and clarity ( r [20] = 0.39) were moderately related to improvements in emotional eating. While several components of emotion-focused treatments may improve outcomes, each component may demonstrate a unique mechanism of action. Further study is needed to isolate these treatment components in fully powered clinical trials to better understand the mechanisms of action for emotion-focused treatments and ultimately develop more efficient and effective treatment approaches.